Postmenopausal Hormone Replacement Therapy (HRT) May Cause Dementia: Are There Alternatives? - Doepp, Manfred (British Journal of Healthcare and Medical Research, 2024)
Based on recent observations and a study in which it was found that postmenopausal hormone replacement therapy (HRT) can cause an increased incidence of dementia, the question arises as to the causes of this and the purpose of this therapy. According to our experience, it can be assumed that these negative effects occur with chemical-artificial hormone replacement, since these are not identical with endogenous hormones. We contrast this with the existing possibilities of nature-identical treatments using the prohormone pregnenolone and agents of plant origin. So far we have not experienced any case of dementia with them.